Crianças do hoje, gestoras do amanhã: uma análise das concepções de sustentabilidade de estudantes do ensino fundamental I, e das práticas de EPS de uma escola paraibana - Silva, Arthur William Pereira da (2018)
Sustainability and sustainable development are topics that have been widely debated and fostered since the end of the 20th century, when several world leaders turned their attention to the unsustainability of the dominant economic model. However, this form of development will only become possible through education for sustainability, in which people must have access to the principles of sustainability, in order to transform their decision-making models, their habits and customs, thus becoming co-creators of a sustainable society. Aiming to contribute to the improvement of actions aimed at education for sustainability, as well as the training of sustainable individuals, the objective of this research is to analyze the concepts of sustainability of elementary school students I in a school organization in Paraiba. Furthermore, in order to achieve this goal, the following specific objectives were proposed: To contextualize the school and its specificities in relation to education for sustainability; to map the conceptions of elementary school students' sustainability based on their experiences, especially in the context of their education; to identify how the variation of conceptions of sustainability behaves in elementary school students; to identify how sustainability education is developed at the school under study, and how the education for sustainability strategies and practices developed at that school can be improved. The current research follows the assumptions of the interpretative paradigm and is qualitative in nature. The main method of research is the phenomenological analysis with the use of drawings. The school object of the study is the IPEI - Instituto Pessoense de Educação Integrada (Institute for Integrated Education of João Pessoa), in which the students of the 2nd, 3rd and 5th grades of elementary school participated in the study. The results indicate that the school studied, in fact, develops several EPS actions with its students. Regarding the concepts of sustainability, the phenomenological analysis showed six different qualitatively ways of understanding the sustainability of the students who participated in the research, they are: (1) Disconnect; (2) Preservationist; (3) Interventionist; (4) Reconciliation; (5) Socioeconomic-environmental conciliation and (6) Intergenerationalist. It was also possible to perceive that the variation of these conceptions throughout elementary school is ascending, that is, it expands and deepens during the school years. The results also showed that, in relation to how the education for sustainability is developed in the school and how it can be improved, that the institution already fully operates according to 13 of the 23 education for sustainability principles raised through the literature review developed in this academic paper, according to other 08 principles, and 02 principles that are not put into practice yet. That is, although its education for sustainability activities already demonstrate adherence to good part of the guiding principles, there are still dimensions to be improved.